Long‐term seizure outcome following epilepsy surgery in the parietal lobe: a meta‐analysis. Issue 2 (1st June 2018) - Pilipović‐Dragović, Sanja; Ristić, Aleksandar J.; Bukumirić, Zoran; Trajković, Goran; Sokić, Dragoslav
ABSTRACT: Aim . Due to a limited number of patients with drug‐resistant parietal lobe epilepsy in surgical series, there are insufficient data about long‐term seizure outcome following surgery restricted to the parietal lobe. We performed a meta‐analysis to asses long‐term outcomes in patients with parietal lobe epilepsy who underwent surgery confined to the parietal lobe or resection with major involvement of the parietal cortex. Methods . An English language literature search for studies on parietal lobe surgery and outcome was conducted using the MEDLINE database, followed by a manual search based on specific criteria. An inverse variance random effect meta‐analysis model was used to estimate the pooled proportion of Engel Class I. Meta‐regression models were used to examine the association between outcome and potential predictors. Results . The search yielded seven retrospective studies with a total sample size of 253 patients (mean follow‐up: 104.9±74.8 months). Following surgery, Engel Class I surgical outcome was achieved in 62.4% (95% CI: 0.492–0.755). Two independent predictors were identified for positive long‐term outcome: interictal EEG localized to the parietal region ( p =0.007) and the presence of tumour ( p =0.022). Conclusion . Following surgery confined to the parietal lobe or resection with major involvement of the parietal cortex, the long‐term prognosis of patients with parietal lobe epilepsy is favourable.